12 Characterisation of clozapine referrals to a tertiary cardiology unit. (5th June 2017) - Joy, George; Bolstridge, Mark; Whiskey, Eromona; McDonagh, TA; Shergill, Sukhi; Plymen, Carla
Abstract : Introduction: Clozapine is an essential tool in the psychiatric armoury: It is the most effective antipsychotic drug and is recommended standard treatment in those with refractory psychotic disorders. The potential risk of cardiac toxicity means that it is not used as commonly as its effectiveness dictates it should be. We studied referrals to our Cardiology Unit from our linked national psychiatric unit to characterise the cardiac status in these individuals and determine outcome. Methods: Retrospective review of all adult patients on clozapine referred to our cardiology unit over 9 years. Electrocardiograms and echocardiographic data was collected as was mortality data. Students t-test, Mann-Whitney U and linear regression were used to analyse results. Results: 29 patients were seen by cardiology in the outpatient setting, all had a diagnosis of schizophrenia. Mean age 43±12 years; 34% female (n=10; table 1). 59 others underwent diagnostic testing but were never referred for review. Median left ventricular ejection fraction (LVEF) was 52(IQR44%–55%), median HR 98 (IQR85-114bpm). No significant difference in age at review and LVEF, QRS duration, heart rate or QTc interval. There was no significant relationship between duration on clozapine and LVEF (p=0.77) at review. There was a significant difference in length of time on clozapine and QTc interval (p=0.02; r=0.46; figure 1). Follow-up time was 4.4 years(IQR 2–6) from initial review; 3 patients died (subarachnoid haemorrhage, aortic aneurysm rupture, suicide). 14 of the surviving 26 (54%) remain on clozapine at most recent follow-up and demonstrated no significant change in the LVEF during this time (p=0.66). Those with LV impairment tended to be seen earlier than those who developed tachycardia without LV impairment (4.7 vs 7.2 years; p=0.27). Patients in the former group were far more likely to have clozapine discontinued compared to those in the tachycardia group (p=0.03). Discussion: Clozapine use is associated with persistent tachycardia, myocarditis and cardiomyopathy; the latter carry significant morbidity and mortality. Despite being very effective, many will have clozapine stopped if there is evidence of cardiac toxicity. Our experience suggests that the short-medium term outcome in these patients is acceptable with very low cardiac risk and no observable deterioration in LVEF. Our findings support two distinct modes of cardiac toxicity. The underlying pathophysiology is not yet well defined and is likely to include patient-specific factors. Our data supports the feeling that tachycardia represents a benign process as all our patients had normal LVEF at the time of review. Prospective studies are required in this complex group; the significance of QTc prolongation with clozapine use remains unclear and further study is warranted. We suggest that these patients should be managed in an interdisciplinary manner with close liaison between cardiologists and psychiatrists.